2015
DOI: 10.1515/pjph-2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Knowledge of Pregnant Women

Abstract: Introduction. Rational nutrition of women during pregnancy has a great influence on the developing fetus. In the properly developing pregnancy, woman should eat 3-4 quality meals per day. What is more, for the proper development of the fetus, as well as the placenta, uterus and the mammary gland, it is necessary to consume high-value protein products. Moreover, vitamins and mineral compounds are important due to the serious implications that arise if not properly provided.Aim. The aim of the paper is to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Only 5.7% consumed alcohol either as beer or wine similar to a Polish study that reported consumption of alcohol to be rare among its respondents. [ 1 ] Other Nigerian studies conducted in Imo state (19%) and Port Harcourt (20%) reported higher rates of consumption of alcohol among pregnant women. [ 8 19 ] Alcohol consumption should be discouraged especially during pregnancy because it can cause fetal alcohol syndrome in the fetus leading to irreversible mental and physical retardation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 5.7% consumed alcohol either as beer or wine similar to a Polish study that reported consumption of alcohol to be rare among its respondents. [ 1 ] Other Nigerian studies conducted in Imo state (19%) and Port Harcourt (20%) reported higher rates of consumption of alcohol among pregnant women. [ 8 19 ] Alcohol consumption should be discouraged especially during pregnancy because it can cause fetal alcohol syndrome in the fetus leading to irreversible mental and physical retardation.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate nutrition during crucial periods of fetal development resulting from poor dietary habits may lead to reprogramming within fetal tissues and pose as a risk factor for non-communicable diseases in later life. [ 1 ] Fetal malnutrition can result from either a surplus or deficiency in the mother. Surpluses result in overweight and complicate pregnancy and labor, leading to serious birth defects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nieco odmienne dane uzyskali Książek i wsp. -w przeprowadzonych przez nich badaniach mało która ciężarna deklarowała spożywanie tego rodzaju napoju [4]. W badaniach własnych oceniano również subiektywne opinie ankietowanych na temat prawidłowego żywienia kobiet w okresie ciąży.…”
Section: Dyskusjaunclassified
“…w okresie dzieciństwa i w życiu dorosłym. W czasie ciąży następuje wzrost zapotrzebowania na energię, składniki odżywcze, witaminy i składniki mineralne [1,2,3,4], dlatego szczególnie ważne jest wdrożenie w życie zasad racjonalnego żywienia [2]. Istotne jest również ograniczenie lub całkowita rezygnacja ze stosowania używek i wybranych produktów spożywczych [2,5].…”
unclassified